Developing Electronic-Based Maternal and Child Health Monitoring - Riska Rosita; Tominanto, Tominanto; Farida, Siti; Yulianto, Andi; Husin, Husna Sarirah (Journal of Maternal and Child Health, 2024)
Background: The first 1,000 days of life, encompassing fetal development during pregnancy (approximately 270 days) through the child's second year (approximately 730 days), represent a critical window for the development of vital organs, as well as cognitive and motor functions. Optimal monitoring during this period is essential for ensuring healthy growth and development. This study aimed to develop an electronic-based monitoring tool for maternal and child health, designed to deliver comprehensive, accurate, and timely information to facilitate early detection of health risks and support evidence-based interventions. Subjects and Method: The study was conducted using the Rapid Application Development (RAD) approach, which includes the stages of planning, design workshops, and implementation. The tool is intended to be used by health cadres at integrated health posts (posyandu) to support maternal and child health monitoring. Results: A simple and user-friendly electronic-based program has been developed to record and monitor maternal and child health status over time. Users can input the results of maternal and child health assessments, which are then presented in graphical form and can be printed as needed. The application received a feasibility score of 89.8% based on the PIECES framework, indicating strong potential for practical implementation. Conclusion: Graphical representations in maternal and child health applications allow for easier monitoring of examination results. These visual tools enable early identification of potential malnutrition-related risks, such as stunted growth in children, thereby supporting timely intervention and prevention efforts.